THE EFFECT OF OWNERSHIP CONCENTRATION AND LEVERAGE AGAINST EARNINGS MANAGEMENT WITH FIRM SIZE AS A MODERATING VARIABLE - Elly Septiana; Ruhul Fitrios; Supriono Supriono (Jurnal Akuntansi, 2023)
This research aims to assign the respective effects of ownership concentration, and leverage on earnings management with firm size as the moderating variable. There are 12 data on State-Owned Companies Listed on the Indonesia Stock Exchange from 2017 to 2020 which were used as research data samples so 48 samples were obtained using the purposive sampling method. This is study uses data analysis techniques use the Eviews.12 Student Lite program. The results of the partial test (t-test) show that ownership concentration and leverage have an effect on earnings management. The output of the MRA test prove that firm size is able to moderate the relationship between leverage and earnings management. However, this research does not prove that firm size is capable to moderate the respective intercourse between ownership concentration in earnings management.